SISTEM FEDERAL DAN KEMUNGKINAN PENERAPAN DI INDONESIA - Nurjaman, Asep (Jurnal Bestari, 1998)
The balance of powers inherent in this relationship has been of particular significance in Indonesia because of the size and island nature of the country, the large and unbalanced ditribution of the population and mareked ethnic, religious and ecological differences that exist in the different areas. Not suprisingly, different periods have seen defferent approaches to meeting the requirenments of goverment in such a diverse counry.